Open-path dual-comb spectroscopy of methane and VOC emissions from an unconventional oil well development in Northern Colorado - Mead, Griffin J.; Waxman, Eleanor M.; Bon, Daniel; Herman, Daniel I.; Baumann, Esther; Giorgetta, Fabrizio R.; Friedlein, Jacob T.; Ycas, Gabriel; Newbury, Nathan R.; Coddington, Ian; Cossel, Kevin C. (Frontiers in Chemistry, 2023)
We present results from a field study monitoring methane and volatile organic compound emission near an unconventional oil well development in Northern Colorado from September 2019 to May 2020 using a mid-infrared dual-comb spectrometer. Uniquely, this instrument allowed quantification of methane, ethane, and propane in a single measurement with high time resolution and integrated path sampling. Using ethane and propane as tracer gases for methane from oil and gas activity, we observed emissions during the drilling, hydraulic fracturing, millout, and flowback phases of well development. Large emissions were seen in drilling and millout phases and emissions decreased to background levels during the flowback phase. Methane plumes from a nearby landfill were distinguished from the well site using differences in the ethane/methane mixing ratios.